Immittance Spectroscopy of Smart Components and Novel Devices - Mohammad A. Alim; Sanjida Khanam; Martin A. Seitz (Active and Passive Electronic Components)
AC small-signal immittance spectroscopy is employed as a viable tool to demonstrate electrical characterization, performance improvement, and quality assurance issues of smart materials-based components and novel devices. The variation in the ac response, complemented via dc measurements within a range of tolerating temperature, delineates competing phenomena occurring in the microstructures of these engineering material systems. The results are presented in a generic manner with possible explanations on the mechanisms for two selected Debye-like (nearly ideal) and non-Debye (non-ideal) low-capacitance resistors. This spectroscopic approach allows systematic development of a representative equivalent circuit, considered to be the characteristic of the devices and components, for specific applications.